Effects of the exogenous N-acylhomoserine lactones on the performances of microalgal-bacterial granular consortia. Issue 1 (31st December 2022) - Lyu, Wanlin; Zhang, Shujia; Xie, Yijia; Chen, Rongfan; Hu, Xiaoling; Wang, Bin; Guo, Wenbin; Wang, Hongyu; Xing, Jie; Zhou, Dao
ABSTRACT: Chlorella sorokiniana, the dominant microalgal strain with fast growth rate and high nutrients' adsorption rate, was selected from the mature MBGS system. After adding C6-HSL and 3-oxo-C12-HSL to the MBGS consortia formed by combining it with mature AGS, it could also be found that C6-HSL accelerated the denitrification rate and improved the removal rate of TIN and TP effectively. Besides, the promoting effect of C6-HSL was slightly higher than that of 3-oxo-C12-HSL. By adjusting the concentration of C6-HSL (5 × 10 −9, 7.5 × 10 −7 and 2.5 × 10 −5 mol/L), the results revealed that adding 5 × 10 −9 mol/L C6-HSL significantly improved the efficiency of nitrogen and phosphorus removal in MBGS consortia. However, adding higher concentration of C6-HSL (7.5 × 10 −7 mol/L) would lead to deterioration of TIN and COD degradation. The content of EPS secreted by bacteria was regulated by different concentrations of AHLs, and the PS/PN value decreased with the increasing trend of C6-HSL concentration. GRAPIHCAL ABSTRACT: uf0001